FADS2 confers SCD1 inhibition resistance to cancer cells by modulating the ER stress response - Ikeda, Toshikatsu; Katoh, Yuki; Hino, Hirotsugu; Seta, Daichi; Ogawa, Tadashi; Iwata, Takashi; Nishio, Hiroshi; Sugawara, Masaki; Hirai, Shuichi (Scientific reports, 2024)
Stearoyl-CoA desaturase 1 (SCD1) is an attractive target for cancer therapy. However, the clinical efficacy of SCD1 inhibitor monotherapy is limited. There is thus a need to elucidate the mechanisms of resistance to SCD1 inhibition and develop new therapeutic strategies for combination therapy. In this study, we investigated the molecular mechanisms by which cancer cells acquire resistance to endoplasmic reticulum (ER) stress-dependent cancer cell death induced by SCD1 inhibition. SCD1 inhibitor-sensitive and -resistant cancer cells were treated with SCD1 inhibitors in vitro, and SCD1 inhibitor-sensitive cancer cells accumulated palmitic acid and underwent ER stress response-induced cell death. Conversely, SCD1-resistant cancer cells did not undergo ER stress response-induced cell death because fatty acid desaturase 2 (FADS2) eliminated the accumulation of palmitic acid. Furthermore, genetic depletion using siRNA showed that FADS2 is a key determinant of sensitivity/resistance of cancer cells to SCD1 inhibitor. A549 cells, an SCD1 inhibitor-resistant cancer cell line, underwent ER stress-dependent cancer cell death upon dual inhibition of SCD1 and FADS2. Thus, combination therapy with SCD1 inhibition and FADS2 inhibition is potentially a new cancer therapeutic strategy targeting fatty acid metabolism.